Invariant NKT cell serves as a novel therapeutic target for control of obesity. (February 2013) - Iwabuchi, Kazuya; Satoh, Masashi
Evaluation of: Lynch L, Nowak M, Varghese B et al. Adipose tissue invariant NKT cells protect against diet-induced obesity and metabolic disorder through regulatory cytokine production. Immunity 37(3), 574–587 (2012). Recent studies have revealed that not only macrophages but also T lymphocytes play active roles in the development of obesity in either an aggravating or ameliorating direction. NKT cells, a subset of innate T lymphocytes, recognize lipid antigens in the context of a nonpolymorphic MHC class I-like molecule, CD1d, implying that NKT cells are likely to participate in the process. Lynch et al. demonstrated that obese patients showed reduced NKT cell count and the reduction of body fat through therapeutic intervention induced the recovery of NKT cells. They attempted to test whether the manipulation of NKT cells (deficiency and stimulation with ligands, among others) could affect adiposity in vivo and demonstrated that NKT cells did indeed play ameliorating roles in the development of obesity, partially through a production of anti-inflammatory cytokines.